1992
DOI: 10.1111/j.1432-1033.1992.tb17138.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of a membrane tyrosine phosphatase activity by somatostatin analogues in rat pancreatic acinar cells

Abstract: A phosphoryl protein tyrosine phosphatase (PTPase) activity has been characterized in rat pancreatic acinar membranes using 32P-labeled poly(Glu,Tyr) as substrate. Acinar membranes exhibited a high affinity for the substrate, with an apparent K , of 0.46 pM and an apparent V,,, of 0.9 nmol . mg protein-. min-Acinar membrane PTPase activity displayed specific characteristics of other PTPases; it was inhibited by the inhibitors Zn2+, orthovanadate and by the divalent cations Mn2+ and Mg2+, and was stimulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…We and others have demonstrated that somatostatin and analogues induce the stimulation of a membrane PTPase, which may be involved in the inhibitory effect of these peptides on cell proliferation (9,11,12,38). More recently, we have established the role of the somatostatin receptor sst2 in mediating the stimulatory effect of somatostatin on PTPase activity and its negative effect on cell growth (13,14).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We and others have demonstrated that somatostatin and analogues induce the stimulation of a membrane PTPase, which may be involved in the inhibitory effect of these peptides on cell proliferation (9,11,12,38). More recently, we have established the role of the somatostatin receptor sst2 in mediating the stimulatory effect of somatostatin on PTPase activity and its negative effect on cell growth (13,14).…”
Section: Discussionmentioning
confidence: 96%
“…In pancreatic tumor cells, we and others have previously shown that somatostatin and analogues antagonize the mitogenic effect of growth factors acting on tyrosine kinase receptors such as epidermal growth factor (9,10). Although the molecular events leading to the inhibition of cell proliferation are still poorly understood, it has been shown that, after binding to somatostatin receptors, somatostatin analogues cause a rapid stimulation of a membrane proteintyrosine phosphatase (PTPase) 1 activity and dephosphorylate phosphorylated epidermal growth factor receptors (9,11,12) suggesting that a PTPase may participate in the somatostatininduced inhibition of growth factor-mediated mitogenic signal. Recently, the expression of the sst2 somatostatin receptor subtype in NIH3T3 and Chinese hamster ovary (CHO) cells led us to the demonstration of the direct involvement of sst2 in both the antiproliferative effect of somatostatin and its stimulatory effect on PTPase activity (13,14).…”
mentioning
confidence: 99%
“…We report evidence that only SSTR2 and -5 mediate the inhibition of cell proliferation induced by RC-160 and that these two receptor subtypes are coupled to distinct signal transduction pathways. The activation of a tyrosine phosphatase and the inhibition of calcium mobilization mediated, respectively, by SSTR2 and Abbreviations: S-14, somatostatin-14; SSTR1 to -5, somatostatin receptor subtypes 1 (22). After the CHO cells were grown in 75-cm2 flasks for 48 h, the cells were washed with ice-cold aMEM, scraped off, and resuspended in aMEM containing bovine serum albumin (1 mg/ml) and soybean trypsin inhibitor (0.3 mg/ml).…”
mentioning
confidence: 99%
“…After centrifugation at 10,000 x g for 30 sec, aMEM was removed and cells were quickly lysed in liquid nitrogen in 50 mM Tris-HCl (pH 7.4) containing soybean trypsin inhibitor (0.3 mg/ml) and 0.1 mM phenylmethylsulfonyl fluoride. After thawing, the homogenate was assayed for the tyrosine phosphatase activity in 100 ,ul containing 50 mM Tris HCl (pH 7.0), bovine serum albumin (1 mg/ml), 30,000 cpm of 33P-labeled poly(Glu, Tyr), 1 gg of protein, and 5 mM dithiothreitol as described (10,22 …”
mentioning
confidence: 99%
“…Binding of [ 125 I-Tyr 11 ]SS was performed on rat pancreatic acinar membranes by a modification of the method of Colás et al [7]. Tyr 11 -SS was radioiodinated by the chloramine-T method as described by Greenwood et al [15].…”
Section: Binding Of [ 125 I-tyr 11 ]Ssmentioning
confidence: 99%